Productivity growth, catchability, stock assessments, and optimum renewable resource use. (December 2015) - Squires, Dale; Vestergaard, Niels
Abstract: Productivity growth substantially impacts rent-maximizing resource stocks, and can lead to an economic optimum that has overfished stocks: BMEY<BMSY. Bioeconomic models can give biased results and policy advice when not accounting for time-varying catchability—notably due to productivity growth—and density-dependent catchability, and not distinguishing between fishery-dependent and fishery-independent data and implications for catchability, modeling, and applicability of results. Productivity growth, as a component of time-varying catchability, also impacts stock assessments. CPUE standardization and productivity measurement both face an identification issue in disentangling changes in resource stocks from changes in productivity as well as endogenous regressors for which there are potential identification strategies. An empirical example illustrates BMEY<BMSY. Highlights: Growth in productivity or fishing power impacts catchability and economically optimum exploitation of marine capture fisheries. Stock assessments aim to remove the effect of productivity growth from stock estimates. Economists want to remove the effect of stock changes from productivity growth. An identification strategy is required to disentangle the two sources of change, often using the same fishery-dependent data. The North Pacific Albacore troll fishery illustrates the effects of productivity growth on economically optimum stock size.